Clinicopathologic Characteristics and Prognosis of Glycogen‐Rich Clear Cell Carcinoma of the Breast. Issue 2 (9th January 2014) - Ma, Xiangmin; Han, Yunwei; Fan, Yu; Cao, Xuchen; Wang, Xin
Abstract Glycogen‐rich clear cell carcinoma (GRCC) of the breast is a rare type of breast carcinoma. Knowledge about the characteristics of this type is fragmentary, and the prognosis is on debate. In this study, we aimed to summarize the clinical, pathologic, and biologic characteristics of GRCC of the breast and analyze the survival. We reviewed the cases of breast cancer in our hospital between January 1999 and December 2009 and identified 28 patients as GRCC of the breast. The routine hematoxylin–eosin staining, periodic acid‐Schiff (PAS) staining, and diastase PAS staining were performed on the tumor tissues. The expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER‐2), Ki67 and P53 were evaluated by immunohistochemistry. Tumors with a HER‐2 score of 2+ were confirmed by fluorescent in situ hybridization test. Each GRCC case, who had complete follow‐up data, was compared with four cases of usual invasive ductal carcinomas as controls in the same database and matched with age, year of diagnosis, tumor size, nodal status, and immunophenotype. The chi‐squared test and the Fisher's exact test were used to compare the characteristics of GRCC cases and controls. The univariate analysis was used to study the prognosis, and Kaplan–Meier method was used to compare the survival of two groups. The clinicopathologic and imaging features were analyzed in the GRCC cases. Tumor sizes ranged from 0.8 to 7.5 cm (mean, 3.2 cm). Thirteen cases (46.4%) had positive lymph nodes. The positivity of ER and PR was 61.5% (16 of 26). HER‐2 was positive for three cases (12%). The positivity of Ki67 and P53 were 87.5% and 45.8%, respectively. Twenty‐four cases were followed up from 19 to 158 months. The prognosis of GRCC of the breast was significantly related with the number of positive lymph nodes (p < 0.001), and patients with more than 10 positive lymph nodes were at high risk of recurrence or metastasis. There was no significant difference in overall survival (p = 0.547), and disease‐free survival (p = 0.900) between GRCC of the breast and the usual invasive ductal carcinomas. GRCC of the breast may not have a worse survival.